Humanism Education Model at Rama Park School, Denpasar - Ni Wayan Karmini (Green Publisher Indonesia, 2022)
This article aims to discuss the humanism education model and its implementation in learning process at Taman Rama Elementary School, Denpasar. Data acquisition was carried out through literature study, observation, and interviews with education observers, student parents, and managers of Taman Rama Elementary School, Denpasar. The collected data were analyzed descriptively by applying the humanism learning theory. The study results show that Taman Rama Elementary School students' character building is carried out by applying the neo-humanistic education model, which is a horizontal balance between physical development and mental development. Besides that, vertically in the form of achieving spiritual development's process. The humanism education process implemented in Taman Rama Elementary School, Denpasar was pursued by implementing the 2013 curriculum which led students to have a humanistic personality and have multiple intelligences. The intelligence referred to is kinetic intelligence, intellectual intelligence, social intelligence, emotional intelligence, and spiritual intelligence by upholding the principle of non-violence (ahimsa). This means that students are expected to have noble humanitarian traits and attitudes, namely simplicity, care for others, and the environment. In addition, it also encourages students to be active, creative, disciplined, and responsible.